Influence of Y doping on high temperature oxidation resistance of titanium diboride coatings - Xiaolong Yao; Wei Dai; Qimin Wang; Junfeng Wang (Journal of Materials Research and Technology)
In this study, DC magnetron sputtering was employed to deposit TiB2 coatings with varying yttrium content. The XPS results revealed that yttrium was identified in the TiB2 coating as yttrium oxide (Y2O3) due to the presence of residual oxygen. The highest hardness of 39.5 GPa, observed in the coating with 0.51 at.% Y, was attributed to the addition of Y, which promoted the grain refinement and increased the coating structural density. The oxidation activation energy measurements indicated that the Y-doped TiB2 coatings exhibited enhanced thermal stability compared with the pure TiB2 coatings, with the stability improving as the yttrium doping increased. When oxidized at 600 °C for 4 h, an oxide scale of 1.97 at.% Y coating was reduced by 50.3 % compared to the pure TiB2 coating, confirming the enhanced oxidation resistance of Y-doped coatings. An amorphous layer (Y–O–Ti) at the interface between the oxide and unoxidized layers inhibited oxygen diffusion, thus limiting the oxidation rate. Thermodynamically, Y2O3 in the TiB2 coating delayed the transition from metastable anatase TiO2 to stable rutile TiO2, enhanced the thermal stability of the B2O3, and retarded internal oxygen diffusion, thereby synergistically improving the oxidation resistance.